Investigation Of 3D Printing Parameters On The Mechanical Properties Of Polymer Composites (International Journal of Environmental Sciences, 2025)
Experimental investigation of 3D printing parameters on the mechanical behaviour of polymer composites is imperative for the optimization of material performance for additive manufacturing. In the present study, the effects of influential Fused Deposition Modelling (FDM) parameters such as layer height, infill density, raster direction, nozzle temperature, and printing speed on tensile strength, flexural characteristics, and impact resistance are examined. Further, the contribution of reinforcement materials like carbon fibers, glass fibers, graphene, and boron nitride and thermosetting agents like phenolic resins in reinforcing the structural properties of printed composites is investigated. The research also assesses the optimization techniques such as computational modelling, machine learning algorithms, and post-processing treatments to address issues such as anisotropic behaviour and weak interlayer bonding. Results show that the optimization of printing parameters and reinforcement materials greatly enhances mechanical performance, allowing for wider applications in automotive, aerospace, and biomedical engineering. Recent advances and challenges in thermoplastic reinforced thermosetting polymer composites for various applications also being discussed. Future studies should aim at hybrid reinforcements and green materials for greater efficiency and durability in 3D-printed polymer composites.